Paweł Jasienica and Polish Writers’ Union - Rokicki, Konrad (Sensus Historiae, 2019)
Paweł Jasienica, the widely popular and recognized Polish author, became the object of a anti-intellectual witch hunt in 1968. In the 1950 and 1960s, Jasienica was one of the central figures in the writers’ milieu, who began to openly resist the Party cultural policy, in particular protesting against censorship restrictions. He was one of the signatories of the Letter of the 34, signed by eminent academics and writers in protest against violating the constitutional guarantee of freedom of expression. Jasienica organized an extraordinary session of the Polish Writers’ Union convened in defense of the production of the national drama Dziady (forefathers), which was banned by the authorities. At the same time, he also publicly condemned anti-Semitism. Attacked by the First Party Secretary in his speech, Jasienica fell victim to a press with hunt. Furthermore, he was not allowed to clear his name of insinuations of murder and treason. Instead of defending him, the leadership of the Polish Writers’ Union initiated the formal procedure to expel him from the organization.